Prioritization for the development of clinical practice guidelines in the Seguro Social de Salud del Peru (EsSalud): multicriteria analysis - Suárez, Victor (2018)
Objectives. To describe the prioritization process for developing the clinical practice guidelines (GPC) in the Seguro Social del Peru (EsSalud). Methods. The prioritization process was carried out through a multicriteria analysis in three steps: identify the variables, obtain information from them and assign them a weighting. Finally, an ordered list was obtained that was put to the consideration of the policy makers. Results. The five diseases with the highest number of DALY (disability adjusted life year) were osteoarthritis, glaucoma, schizophrenia, osteoporosis and pathological fractures, and diabetes mellitus. The most spending for drugs were hemophilia, the nephritis group, nephrosis (mainly chronic renal failure), rheumatoid arthritis, breast cancer and AIDS. Priority diseases from the point of view of the services offered were those with high mortality and high disability. Conclusions. This is the first process of guidelines prioritizing in Peru. The first 5 diseases prioritized were: osteoarthritis, diabetes mellitus, glaucoma, chronic kidney disease and lumbago.